2006
DOI: 10.1093/molehr/gal080
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in the expression of superoxide dismutases and catalase are associated with ultrastructural modifications in human granulosa cells

Abstract: Limited knowledge exists about changes in follicle quality associated with age. The aim of this work was to investigate whether ageing may cause oxidative stress-mediated alterations in human granulosa cells (GCs) from periovulatory follicles. GCs employed in this study were obtained from follicular aspirates of 20 younger women (range 27-32 years) and 20 older women (range 38-41 years) undergoing an IVF treatment. Results obtained from comparative RT-PCR analysis revealed that the mean relative levels of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 31 publications
8
102
1
Order By: Relevance
“…The correlation between patients' age and log2 expression values for genes related to oxidation-reduction process, regardless of therapy, is not statistically significant. A negative correlation between age and gene expression of genes involved in defense against reactive oxygen species (ROS) in follicles is well known and has been reported in several studies [28][29][30][31]. It seems that in our study we have controlled this effect by including patients of similar age and younger than 35 years, which is proved by a non-significant correlation (Table S3-Regardless of therapy).…”
Section: Discussionmentioning
confidence: 86%
“…The correlation between patients' age and log2 expression values for genes related to oxidation-reduction process, regardless of therapy, is not statistically significant. A negative correlation between age and gene expression of genes involved in defense against reactive oxygen species (ROS) in follicles is well known and has been reported in several studies [28][29][30][31]. It seems that in our study we have controlled this effect by including patients of similar age and younger than 35 years, which is proved by a non-significant correlation (Table S3-Regardless of therapy).…”
Section: Discussionmentioning
confidence: 86%
“…In aging cells, high amount of reactive oxygen species (ROS) are usually generated due to age-associated decrease in mitochondrial quality. A decrease in the levels of SOD1, SOD2, and catalase mRNA and protein in granulosa cells derived from antral follicles of older women (≥38 years) has been reported [18]. In addition, p38 MAPK was more extensively phosphorylated in the granulosa cells derived from older women (>36) than those derived from younger patients, and the activation and cytoplasmic localization of p38 MAPK in granulosa cells derived from older women was indicative of oxidative stress [20].…”
Section: Discussionmentioning
confidence: 94%
“…Oocyte growth is supported by surrounding granulosa cells [17], and a deterioration in the characteristics of these granulosa cells derived from full-grown antral follicles have been observed in aged women and cows [18][19][20][21]. Result from real time RT-PCR experiments have revealed that the expression of some genes including those that encode for antioxidants in mouse ovary was affected by aging [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a delicate balance between ROS and antioxidant enzymes in the ovarian tissue (Shiotani et al 1991;Behrman et al 2001;Sugino et al 2004;Agarwal et al 2005;Agarwal et al 2006;Tatone et al 2008). The imbalance of ROS and antioxidants has been suggested as a mechanism of ovarian aging, as shown by decreased levels of glutathione and glutathione S-transferase in ovulated oocytes from aged mouse or downregulation of superoxide dismutase (Cu/ZnSOD and MnSOD) and catalase genes in human granulosa cells (Tarin et al 2004;Tatone et al 2006;Tatone et al 2008). Under these conditions, increased redox-active iron in aged ovaries would be a pro-oxidant for the generation of toxic ROS such as hydroxyl radicals, resulting in a loss of the balance between ROS and antioxidants.…”
Section: Discussionmentioning
confidence: 99%